DYNAMIC PHYSIOLOGICAL OUTPUT DURING SURGERY AS A PREDICTOR OF POST-OPERATIVE RESILIENCE. (11th November 2018) - Lipsitz, L; Whitson, H; Berger, M; Giattino, C; Zhou, J; Woldorff, M
Abstract: The proportion of surgical patients over age 65 is increasing, and older patients who receive surgery and anesthesia are at higher risk of complications and poor functional and cognitive recovery. We will introduce a clinical test paradigm in which the surgery itself serves as the experimental stressor, with future recovery predicted by the response of dynamic physiological output measures (e.g., heart rate, electroencephalogram [EEG]) observed during the surgery. This approach is valuable for risk stratification and medical decision-making, especially when surgery is necessitated without opportunity for extensive pre-operative assessment. We will review the prognostic significance of three types of resilience indicators that can be derived from intraoperative time series physiological output data: heart rate variability, "anteriorization" of the EEG alpha band, and multi-scale entropy (an indicator of data complexity). We will present pilot data from a cohort of older adults undergoing non-cardiac, non-neurological, elective surgeries at a single center.